Habit Persistence, Nonseparability between Consumption and Leisure, or Rule-of-Thumb Consumers: Which Accounts for the Predictability of Consumption Growth? - Kiley, Michael T (The Review of Economics and Statistics, 2010)
Consumption growth is predictable, a basic violation of the permanent-income hypothesis. This paper examines three possible explanations: rule-of-thumb behavior, in which households allow consumption to track per period income flows rather than permanent income; habit persistence; and nonseparability in preferences over consumption and leisure. The results illustrate that weak instruments make the results highly sensitive to some arbitrary choices common in the literature. Using a technique that is robust to instrument choice, the analysis shows support for habit persistence and rule-of-thumb behavior and little support for nonseparability between consumption and leisure.